Letter : Food for Spain - Stolz, George
029-0037-001 INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU Sch/H TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter No. 19th January, 1938. Dear Comrade Tewson, Food for Spain We have carefully noted your telephone communication of to-day, regarding the consignment of goods to Spain, and we will let you have a reply on Friday, when our General Secretary, who is dealing with this matter but who is at the moment absent from Paris, will have returned. Yours sincerely, G. Stolz, Assistant Secretary: 292/946/29/37